The dual role of women in raising family social status through education: A perspective of Edward Wilson’s nurture theory - Nur Laili, Rizki; Listyani, Refti Handayani; Agzumi, Gita (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
Most women agree that their responsibilities and position within the family are crucial to what women do today. The purpose of this study is to identify the influence of education on the improvement of the social status of women and their families, as well as how education is a key factor in social mobility in Nurture theory. This study employs a qualitative method with 60 random participants to examine the impact of education on improving women's and their families' social status, as well as its role in social mobility based on Nurture theory. The findings reveal that education enhances social and economic status, provides better job opportunities, and serves as a role model for future generations. However, social and cultural barriers continue to limit women in balancing careers and family life. This study highlights the importance of expanding access to education and challenging gender stereotypes to support women's roles in society.